An overview of technology, guidance and leadership in terms of education (Cambridge Scholars Publishing, 2018)
Education is a necessary process for all age groups, with people having an intimate relationship with it from birth to death. Nowadays, with the development of technology, people are able to access more comfortable education. The most important issue here is that technology is used correctly and properly in education. In this regard, educational trainers have significant duties. If they provide good guidance and leadership to their students, the latter will succeed in their educational life. This book offers several articles on technology, guidance and leadership topics, and, as such, will ser.